2020
DOI: 10.3130/aije.85.277
|View full text |Cite
|
Sign up to set email alerts
|

Operational Strategies for Self-Consumption Considering the Use of an Electric Vehicle in a Net Zero Energy House

Abstract: This study proposes operational strategies for combinations of equipment, including an electric vehicle (EV), in a house using self-consumption.The aim of this is to attain both comfort and efficient energy management under several household and regional conditions, focusing on the frequency of the EV's use as well as the residents' schedules. As operational strategies for self-consumption of surplus power, storage battery (BT) charging, EV charging and daytime operation of heat pump water heater (EC) were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The comparison results indicated that the introduction of a BEV and V2H system has the potential to reduce CO 2 emissions compared with the case of BEVs alone. In addition, Akimoto et al [2] investigated SB charging, BEV charging, and daytime operation of heat pump water heaters as operational methods for the self-consumption of PV surplus electricity and compared the effects of installing each device. The results showed that households with less frequent use of vehicles and shorter driving distances have higher self-consumption of PV surplus power and lower CO 2 emissions and annual costs, whereas households with more frequent use of vehicles and longer driving distances cannot fully consume PV surplus power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison results indicated that the introduction of a BEV and V2H system has the potential to reduce CO 2 emissions compared with the case of BEVs alone. In addition, Akimoto et al [2] investigated SB charging, BEV charging, and daytime operation of heat pump water heaters as operational methods for the self-consumption of PV surplus electricity and compared the effects of installing each device. The results showed that households with less frequent use of vehicles and shorter driving distances have higher self-consumption of PV surplus power and lower CO 2 emissions and annual costs, whereas households with more frequent use of vehicles and longer driving distances cannot fully consume PV surplus power.…”
Section: Introductionmentioning
confidence: 99%
“…; h is the hour [0-23]; m is the month[1][2][3][4][5][6][7][8][9][10][11][12]; d is the day category [weekday, holiday]; w is the weather category [sunny, other]; r is the discount rate [%]; vtd is the durable years of each vehicle type [years]; pvd is the durable years of PV power [years]; sbd is the durable years of the SB [years]; T is the sales volume of vehicle type [units]; PVA is the PV installation area [m 2 ]; SBC is the storage capacity [kWh]; AC is the annual costs [million yen]; ACE is the annual CO 2 emissions [t-CO 2 ]; TC is the installation cost of vehicles and equipment [million yen]; EC is the energy cost [million yen]; CC is the carbon cost for CO 2 emissions [million yen]; ELCE is the CO 2 emissions from electricity [t-CO 2 ]; GACE is the CO 2 emissions from gasoline [t-CO 2 ]; HYCE is the CO 2 emissions from hydrogen [t-CO 2 ]; VTC is the installation cost of each vehicle type [million yen]; ID is the installation density [kW/m 2 ]; ND is the number of days in each category [days]; ELC is the electricity cost [million yen]; GAC is the gasoline cost [million yen]; HYC is the hydrogen cost [million yen]; ELU is the electricity usage [MJ]; ELP is the electricity price [yen/MJ]; AEC is the amount of electricity for additional charging while driving [MJ]; AGC is the consumption of gasoline used for driving [MJ]; GP is the gasoline price [yen/MJ]; AHC is the consumption of hydrogen used for driving [MJ]; HP is the hydrogen price [yen/MJ]; CP is the carbon tax rate for CO 2 emissions [yen/t-CO 2 ]; ELCI is the CO 2 intensity of electricity [g-CO 2 /MJ]; GACI is the CO 2 intensity of gasoline [g-CO 2 /MJ]; HYCI is the CO 2 intensity of hydrogen [g-CO 2 /MJ]; and GTH is the amount of electricity purchased or sold between the residence and the grid power [MJ].…”
mentioning
confidence: 99%